2022
DOI: 10.3389/fcvm.2022.906753
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and Autophagy-Related Genes in the Pathogenesis of Ischemic Cardiomyopathy

Abstract: BackgroundObesity plays an important role in type 2 diabetes mellitus (T2DM) and myocardial infarction (MI). Ferroptosis and ferritinophagy are related to metabolic pathways, such as fatty acid metabolism and mitochondrial respiration. We aimed to investigate the ferroptosis- and autophagy-related differentially expressed genes (DEGs) that might be potential targets for MI progression.MethodsGSE116250 was analyzed to obtain DEGs. A Venn diagram was used to obtain the overlapping ferroptosis- and autophagy-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Macrophages are involved in all the CAD stages, including the inflammation response in atherosclerosis, heart failure, and MI. [31][32][33][34] CD169+ macrophage or its receptor Mertk deficiency impaired the mitochondria elimination in the early infarction period, therefore, cardiomyocytes autophagy was impaired, mitochondria were accumulated, and ventricular functions decreased. 35 In addition, macrophages facilitate cardiac electrical conduction via Cx43 and Cx43 conditional deletion in macrophages and congenital lack of macrophages delays atrioventricular conduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages are involved in all the CAD stages, including the inflammation response in atherosclerosis, heart failure, and MI. [31][32][33][34] CD169+ macrophage or its receptor Mertk deficiency impaired the mitochondria elimination in the early infarction period, therefore, cardiomyocytes autophagy was impaired, mitochondria were accumulated, and ventricular functions decreased. 35 In addition, macrophages facilitate cardiac electrical conduction via Cx43 and Cx43 conditional deletion in macrophages and congenital lack of macrophages delays atrioventricular conduction.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are involved in all the CAD stages, including the inflammation response in atherosclerosis, heart failure, and MI 31–34 . CD169+ macrophage or its receptor Mertk deficiency impaired the mitochondria elimination in the early infarction period, therefore, cardiomyocytes autophagy was impaired, mitochondria were accumulated, and ventricular functions decreased 35 .…”
Section: Discussionmentioning
confidence: 99%
“…DUSP1-mediated dephosphorylation of JNK has been shown to have an antiapoptotic effect in myocardial ischemiareperfusion (I/R) injury and has been identified as an immunerelated diagnostic biomarker for AMI [32,53,54]. CDKN1A, also called p21, inhibits cardiomyocyte proliferation through acetylation modification in MI and has been proposed as a potential therapeutic target for MI [55,56]. TLR4, a key pattern recognition receptor, is expressed on macrophages and cardiomyocytes and its elevated expression in MI exacerbates ischemic injury to cardiomyocytes [57], participating in multiple inflammatory signaling pathways [58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…CDKN1A, also called p21, has been shown to inhibit cardiomyocyte proliferation by acetylation modi cation in MI [54]. Meanwhile, Zheng Y et al, [55] found CDKN1A may be potential therapeutic targets for patients with MI. TLR4 is a key molecular pattern recognition receptor that is expressed on the cell membrane surface of macrophages and cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%